Valuation and Treatment of Depletable Resources in the National Accounts - Levin, Jonathan (IMF Working Papers; Working Paper ;, 1991)
To assess the feasibility of the national accounts treating as assets depletable resources extracted for sale, the paper examines three issues: 1. whether treating natural resources as assets when they are used requires symmetrical accounting when they enter economic reserves; 2. at what stage between existence in nature and extraction entry to reserves could be counted; and 3. how the value of the in-ground natural resource component could be determined. It suggests treating natural resources entering reserves as 'imports' from the environmental account added to the capital account, registering additions to reserves at a stage involved in economic activities, and valuing reserves by procedures related to market price.